Epidemiegesetz: Entwurf eines Gesetzes zur Neuordnung der Rechtsgrundlagen der Epidemiebekämpfung - Gallon, Johannes; Hollo, Anna-Lena; Kießling, Andrea (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The draft of a new epidemic act proposes new legal bases for managing future epidemics. The standards contained in the IfSG at the beginning of the Corona pandemic were predominantly aimed at reacting to local infectious events and authorized targeted measures. The epidemic demonstrated the need for far-reaching measures to protect life and health of the public. The draft for an epidemic act bundles the practical experiences with the fight against the Corona epidemic as well as the jurisprudential criticism and transfers them with detailed justification into a practical proposal for differentiated legal bases.